The Effect of Information Sharing and Quality on Increasing Consumer Satisfaction at Garut Fighting Sheep Farmers in Garut Regency - RAMADHAN, FAISAL; Nurlina, Lilis; Firman, Achmad (Fakultas Peternakan, Universitas Padjadjaran, 2025)
The cultivation of fighting type Garut sheep is expanding and thriving in West Java, Indonesia, particularly in Garut Regency, necessitating an analysis of efficiency and effectiveness of factors supporting, including information, the aplplication of supply chain management, and productivity to fulfill customer satisfaction. This study aims to assess the impact of sharing information and information quality regarding the implementation of supply chain management and the effect on the process of accelerating the performance of supply chain management, as well as its influence on the process of enhancing the efficiency and effectiveness of supply chain management, with the aim of boosting productivity and achieving customer satisfaction. The research was conducted at Garut Regency in five districts, namely Leles, Tarogong Kidul, Tarogong Kaler, Banyuresmi, and Cilawu. The research method used was survey, and respondents were determined using the Slovin formula. The results showed that Information sharing has no positive and insignificant effect while information quality has a positive but insignificant effect on SCM implementation. SCM implementation variables have a positive and significant effect and information sharing has no positive and insignificant effect on productivity. SCM implementation variables have a positive and significant and productivity and information quality have a positive but insignificant effect on customer satisfaction.